Republic of Equatorial Guinea : Request for an Extended Arrangement Under the Extended Fund Facility and Second Review Under the Staff-Monitored Program-Press Release, Staff Report, and Statement by the Executive Director. (IMF Staff Country Reports; Country Report ;, 2019)
This paper highlights Republic of Equatorial Guinea's Request for an Extended Arrangement Under the Extended Fund Facility and Second Review Under the Staff-Monitored Program. The IMF-supported program aims at maintaining macroeconomic and financial stability, while improving social protection, fostering economic diversification, strengthening governance and fighting corruption. The Equatoguinean economy has been impacted by a sharp decline in oil prices and a secular decline in hydrocarbon output, which led to large macroeconomic imbalances and negative economic growth. Increasing transparency, improving governance and fighting corruption are critical to improve socio-economic outcomes. Structural reforms are expected to play a crucial role in supporting fiscal consolidation and improving growth prospects. The program comprises reforms to the business environment and other reforms to promote economic diversification and support the achievement of sustainable economic growth. Program implementation remains subject to some downside risks, including volatility in hydrocarbon prices, and Public Financial Management (PFM), governance and corruption vulnerabilities.